An Essay about Indigenous Methodology - Porsanger, Jelena (Nordlit, 2004)
In this essay the author intends to articulate methodological issues, which are primarily important for indigenous researchers in the light of the indigenous perspective.
Keywords: epistemology; power relations in research; indigenous research; indigenous methodologies; research ethics